Dynamic risk of coastal flood and driving factors: Integrating local sea level rise and spatially explicit urban growth. (25th October 2021) - Xu, Lilai; Cui, Shenghui; Wang, Xiaoming; Tang, Jianxiong; Nitivattananon, Vilas; Ding, Shengping; Nguyen Nguyen, Minh
Abstract: Coastal flood risk facing urban communities is increasing due to the compound impacts of sea level rise (SLR) and urban growth. Accurate information on future dynamic risk of coastal flooding and its physical and socio-economic drivers is essential for planning effective and targeted adaptation. However, the current scenarios regarding urban development are insufficient to predict the future dynamic spatial distribution of urban socio-economic and physical growth, hindering the exact and dynamic assessment of future coastal flood risk. Moreover, the relative contributions of SLR and urban development to the future dynamics of city-level coastal flood risk have not been examined. Therefore, here we developed a land use-based urban growth scenario for the temporally and spatially explicit simulation of future urban growth in terms of buildings, roads and electrical facilities, and combined it with a local temporally explicit SLR scenario, into a "hazard-exposure-vulnerability" model, for the purpose of dynamic risk assessment of coastal flooding on the urban built environment in Xiamen, China by 2050, and accordingly examined the relative contributions of SLR and urban growth. Our results demonstrated a good performance of the land use-based urban growth model. SLR and urban growth will increase future coastal flood risk (represented by the expected annual damage, EAD) in varying degrees, but their combination is projected to exacerbate future flood damages significantly, indicating that considering either SLR or urban growth in isolation will underestimate future coastal flood risk. Moreover, the relative contributions of SLR and urban growth are dynamic over time, depending on the rate of SLR and the stage of urbanization: for example, the change in coastal flood risk is mainly attributable to urban growth in the phase of rapid urbanization before 2033 in Xiamen, yet the contribution of urban growth then becomes less important compared to SLR, when urbanization slows down, while SLR reaches a threshold after accelerating growth. The approach and results of our study can be considered a decision support tool, to help decision makers assess future coastal flood risk and detect the relative importance of each driving force, in order to employ land use planning, nature-based solutions and engineering protection, to achieve sustainable and resilient coastal cities. Graphical abstract: Image 1 Highlights: Urban growth and sea level rise are integrated, for city-level coastal flood risk assessment. Combination of urban growth and sea level rise drive significant increases in coastal flood risk. Accounting for urban growth and sea level rise separately underestimates coastal flood risk. Relative contributions of urban growth and sea level rise to coastal flood risk are dynamic. Flood-resilient coasts need smart land use planning, green and grey integrated solutions.